WAWASAN HADIS TENTANG NIKAH MUT’AH (Suatu Kajian Mawdhu’iy) - Muhammad Anis Malik (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2015)
This paper examines the perspectives of marriage of mut'ah with a thematic approach. Elaboration of these issues resulted an understanding of mut’ah is a marriage declared running for a certain time. Mut’ah marriage is also known as the al-nikah al-munqati’ (disconnected marriage) and the al-nikah al-muwaqqat (temporary marriage) which became one models of marriage in the early Islam. In the hadith context relating to mut’ah marriage, indicates that there is a conflict between the hadith allowed mut'ah and hadith forbided mut'ah that all are in valid quality. The author offers two methods of settlement apparently contradictory hadith about marriage of mut'ah namely al-jam'u methods and nasikh-mansukh methods that give different legal implications.